Co2+@Mesoporous Silica Monoliths: Tailor‐Made Nanoreactors for Confined Soft Chemistry. Issue 47 (2nd October 2015) - Delahaye , Emilie; Moulin, Robinson; Aouadi, Merwen; Trannoy, Virgile; Beaunier, Patricia; Fornasieri, Giulia; Bleuzen, Anne
Abstract: Mesoporous silica monoliths with various ordered nanostructures containing transition metal M 2+ cations in variable amounts were elaborated and studied. A phase diagram depicting the different phases as a function of the M 2+ salt/tetramethyl orthosilicate (TMOS) and surfactant P123/TMOS ratios was established. Thermal treatment resulted in mesoporous monoliths containing isolated, accessible M 2+ species or condensed metal oxides, hydroxides, and salts, depending on the strength of the interactions between the metal species and the ethylene oxide units of P123. The ordered mesoporosity of the monoliths containing accessible M 2+ ions was used as a nanoreactor for the elaboration of various transition metal compounds (Prussian blue analogues, Hofmann compounds, metal–organic frameworks), and this opens the way to the elaboration of a large range of nanoparticles of multifunctional materials. Abstract : Chemistry in confined space : The elaboration of ordered silica monoliths containing variable amounts of divalent metal cations (see figure) is controlled by the different interactions between the metal species and the structure‐directing polymer P123. The phase diagram of the ternary system metal(II) salt/tetramethyl orthosilicate/P123 is presented and the speciation of the metal cations in the mesoporous monoliths rationalized. The mesoporosity of the monoliths containing accessible M 2+ ions was used as a nanoreactor for the synthesis of various transition metal compounds.